(untitled) (International Journal on Stereo & Immersive Media, 2021)
This paper presents a broad survey examining how the photographic industry in Britain used the patent system, trade-mark and design registration systems to protect and exploit inventions during the nineteenth and early twentieth centuries. It looks at how patents were perceived by the industry, how manufacturers and retailers exploited them, and wider issues which surrounded them, all of which received extensive coverage in the pages of the contemporary photographic press. It does not look at copyright protection for photographs which evolved separately.